2021
DOI: 10.5204/ssj.1623
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Not a Number, I’m Someone to Them”: Supporting Commencing University Students’ Through Technology-Mediated Personalised Communication

Abstract: As universities offer more flexible delivery options there are parallel concerns about increasing levels of engagement. Withdrawal and disconnection from study is most common during the first year of university as students experience social, cultural and financial adjustments and attempt to understand the nuances of academic learning. This article reports on the impact of a technology-enabled support system delivering timely, personalised and actionable feedback on online activity and support emails at critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
0
4
2
Order By: Relevance
“…Although previous research has demonstrated that students have implemented SRL strategies following technology -mediated feedback (e.g., Lewis et al, 2021;Lim et al, 2021), students in the current study did not report increased use of (meta)cognitive learning strategies after technology-mediated feedback. Furthermore, LMS data showed that most students did not implement the suggested strategy outlined in the three emails.…”
Section: Interpretation Of the Findingscontrasting
confidence: 87%
See 3 more Smart Citations
“…Although previous research has demonstrated that students have implemented SRL strategies following technology -mediated feedback (e.g., Lewis et al, 2021;Lim et al, 2021), students in the current study did not report increased use of (meta)cognitive learning strategies after technology-mediated feedback. Furthermore, LMS data showed that most students did not implement the suggested strategy outlined in the three emails.…”
Section: Interpretation Of the Findingscontrasting
confidence: 87%
“…Previous research by Lewis and colleagues (2021) found students felt more motivated and were more likely to engage with course materials following technology -mediated feedback; students also reported a flow on effect of motivation toward their other courses following feedback. Similar to other studies investigating technology-mediated feedback emails (Lewis et al, 2021;Lim et al, 2021), students in the current study r eceived not only emails about the learning strategy, but also general course related emails (e.g., assessment information, due date reminders). These general emails, combined with the tutorial preparation strategy emails, may have been useful more broadly resulting in higher self-reported motivation.…”
Section: Interpretation Of the Findingsmentioning
confidence: 93%
See 2 more Smart Citations
“…In Hall et al's (2018) randomised controlled trial, written reminders were effective in improving mindfulness practice adherence as well as study retention. However, there is also research that suggests students are overwhelmed with information provided through email (Hara, 2000) and discussion forums posts at the start of the semester, and that reminders throughout the semester may be of greater use when they need it most (Lewis et al, 2020). The communication preferences expressed by students versus what has shown to be effective is a balance and demonstrates the complexities in a real-world implementation.…”
Section: Rq3 What Are Students' Perceptions Of Barriers and Motivatio...mentioning
confidence: 99%